CARBON EMISSION (CO2) AND POVERTY ON HUMAN DEVELOPMENT INDEX EVIDENCE IN EAST JAVA - Pipin Nur Ekasari; Suryanto Suryanto (Faculty of Economics and Business, University of Pasundan, 2020)
Carbon emission is exhaust gas that exist around us. According to data estimation of the Intergovernmental Panel on Climate Change (IPCC), carbon emission in Indonesia was 201 million tons and sharply increase in 2024 that will reach 383 million tons. This paper explains about the effect of CO2 emission levels and poverty on the human development index. The data that used is a time series of secondary data within the year of 2012 to 2016 and a cross-sector with 38 regencies in East Java. This research use panel data regressions analysis method. The result concluded that the emissions level in East Java affect positively and significantly towards the human development index. Those, caused by the emission of CO2 levels in East Java still in a good category, means that the environment is still capable of tolerating the emission level. The poverty level effect negatively and significantly into the human development index.